Contextualization of Islamic Education Curriculum in Junior High Schools - Amir Maliki Abitolkha; Ahmad Nur Ismail; Yazid hady (TARBIYA: Journal of Education in Muslim Society, 2020)
AbstractSeveral years of experience teaching PLPG training for teachers in the Ministry of Religion, especially Islamic Religious Education (PAI) teachers, found the fact that "the teacher" as the essential instrument in the process of teaching and learning activities in the classroom is considered unattractive. Therefore, "teachers" are required to design PAI curriculum development and conduct contextual learning on PAI subjects, to be able to connect the material with real-life students. This study aims to explore the relationship between curriculum development and the improvement of PAI contextual learning. The research approach used is descriptive qualitative with a multi-case design carried out at SMPN (Junior High School) 3 Rejoso Darul Ulum and MTsN (Islamic Junior High School) Tambak Beras Jombang. The results showed that; (1) the curriculum development approach commonly referred to and used in both institutions is academic and humanistic. While the technological approach is still unclear. (2) The use of additional PAI literature such as Jurisprudence and Arabic language development, by referring to Fath al-Qarib and Amsilah Tasrifiyah as a form of integration between the formal curriculum in schools and the boarding school curriculum. (3) Factually it can be stressed that the process of curriculum development can increase the contextually of active PAI learning in both educational institutions through the use of project-based learning strategies.AbstrakBeberapa tahun pengalaman mengajar pelatihan Pendidikan dan Pelatihan Profesi Guru (PLPG) untuk guru di Kementrian Agama terutama guru Pendidikan Agama Islam (PAI), ditemukan fakta bahwa “guru” sebagai instrumen terpenting dalam proses kegiatan belajar mengajar di kelas dianggap tidak menarik. Oleh karenanya, “guru” dituntut untuk mendesain pengembangan kurikulum PAI dan melakukan pembelajaran kontekstual pada mata pelajaran PAI, sehingga mampu menghubungkan materi dengan kehidupan nyata siswa. Penelitian ini bertujuan mengeksplorasi hubungan antara pengembangan kurikulum dengan peningkatan pembelajaran kontekstual PAI. Pendekatan penelitian yang digunakan yaitu kualitatif deskriptif dengan rancangan multi-kasus yang dilaksanakan di SMPN 3 Rejoso Darul Ulum dan MTsN Tambak Beras Jombang. Hasil penelitian menunjukan bahwa; (1) Pendekatan pengembangan kurikulum yang biasa dirujuk dan digunakan pada kedua lembaga tersebut adalah pendekatan akademik dan humanistik. Sedangkan pendekatan teknologis masih belum jelas penggunaannya. (2) Penggunaan literatur tambahan PAI seperti Fikih dan pengembangan bahasa Arab, dengan merujuk kitab Fath al-Qarib dan kitab Amsilah Tasrifiyah sebagai bentuk integrasi antara kurikulum formal di sekolah dengan kurikulum pondok pesantren. (3) Secara faktual dapat ditegaskan bahwa proses pengembangan kurikulum dapat meningkatkan kontekstualitas pembelajaran PAI secara aktif pada kedua lembaga pendidikan tersebut melalui penggunaan strategi project based learning. How to Cite: Abitolkha, A. M., Ismail, A. N., Hady, Y. (2020).  Contextualization of Islamic Education Curriculum  in Junior High Schools. TARBIYA: Journal of Education in Muslim Society, 7 (1), 48-66. doi:10.15408/tjems.v7i1.13843.